Las normativas de etiquetado, envasado y embalaje que deben cumplir los productos ecuatorianos para ingresar al mercado de Bolivia. - Cordova Garces, Steeven Josue (My University, 2019)
Currently, companies are faced with new challenges to expand into international markets, but at the same time they initiate a complex process that requires knowing, forecasting and strategies that allow reaching a certain market informed about the requirements and regulations that they require in related aspects. To labeling and packaging regulations. The objective of the research was to analyze the main regulations of labeling, packaging and packaging that Ecuadorian products must meet to enter the Bolivian market. Qualitative research was used with a documentary review in scientific journals, official pages and other online documents that provide information on the standardization of labeling of processed products. In order to solve the reagent, it was determined that companies that export processed foods that wish to export products to the Bolivian market should comply with Bolivian Standard NB 314001 of the Bolivian Institute for Standardization and Quality, Labeling of pre-packaged foods, in which the general conditions are determined, the mandatory information and the obligatory additional requirements in order that Ecuadorian products can enter the Bolivian market without problems. It should be noted that in Ecuador there are Regulations for the labeling of processed products must comply with the requirements of the Ecuadorian Standardization Institute (INEN) and the Andean Countries Regulations, in the case of Bolivia is governed by Emergency Regulation No. 1/78. Ministry of Industry, Commerce and Tourism, Supreme Decree No. 26510 of 02/21/02.
En la actualidad las empresas se encuentran antes nuevos retos de expandirse hacia los mercados internacionales pero a la vez inician un proceso complejo que requiere de conocer, prever y estrategias que permitan llegar a determinado mercado informados sobre los requerimientos y normativas que les exigen en aspectos relacionados a las normativas de etiquetado y embalaje. El objetivo de la investigación fue analizar las principales normativas de etiquetado, envasado y embalaje que deben cumplir los productos ecuatorianos para ingresar al mercado de Bolivia. Se utilizó una investigación de tipo cualitativa con una revisión documental en revistas científicas, páginas oficiales y demás documentos online que brinden información sobre la normalización de etiquetado de productos procesados. Para dar solución al reactivo se determinó que las empresas exportadoras de alimentos procesados que deseen exportar productos al mercado Boliviano deben regirse a la Norma Boliviana NB 314001 del Instituto Boliviano de Normalización y Calidad, Etiquetado de alimentos preenvasados, en la cual se determina las condiciones generales, la información obligatoria y los requisitos adicionales obligatorios con el fin de que los productos ecuatorianos puedan ingresar al mercado boliviano sin problemas. Cabe recalcar que en el Ecuador existen Normas de Regulación en cuanto al etiquetado de los productos procesados deberán cumplir con los requisitos del Instituto Ecuatoriano de Normalización (INEN) y a las Normas de los Países Andinos, en el caso de Bolivia se rige a Norma de Emergencia N° 1/78. Ministerio de Industria, Comercio y Turismo, Decreto Supremo Nº 26510 de 21/02/02.
Keywords: NORMATIVAS; PRODUCTOS PROCESADOS; ETIQUETADO; EMBALAJE; EXPORTACIÓN